Infrared invisibility stickers inspired by cephalopods1. Issue 25 (7th July 2015) - Phan, Long; Ordinario, David D.; Karshalev, Emil; Walkup IV, Ward G.; Shenk, Michael A.; Gorodetsky, Alon A.
<x xml:space="preserve">Abstract</x> The skin morphology of cephalopods endows them with remarkable camouflage capabilities. Herein, we report infrared invisibility stickers inspired by the structures and proteins found in cephalopod skin. These stickers enable arbitrary objects to acquire reconfigurable infrared camouflage patterning. Our work represents an initial step towards wearable biomimetic infrared stealth technologies.